RELEVANSI MATERI AJAR BAHASA JAWA UNTUK SISWA KELAS IV SEKOLAH DASAR DI ERA DIGITAL: ANALISIS BUKU TEKS KURIKULUM MERDEKA - Abdul Arif (Joyful Learning Journal, 2025)
This research aims to conduct an in-depth analysis and evaluation of the relevance of instructional materials in the Grade IV Javanese Language textbook for the Kurikulum Merdeka (Merdeka Curriculum). The analysis encompasses aspects of content, learning activities, and material presentation in relation to the needs of students in the digital era. This study employs a qualitative method with a content analysis approach. The primary data source is the Grade IV Javanese Language textbook for the Kurikulum Merdeka used in Mijen, Semarang City, and the data were collected through documentation techniques. The data were analyzed using a qualitative-interpretive method with an instrument in the form of an analysis sheet developed based on curriculum relevance theory. The results of the research indicate that the textbook's content is dominated by traditional-agrarian themes and does not yet represent the students' digital world. The learning activities presented tend to be passive with minimal technological integration. The unggah-ungguh (Javanese code of polite conduct) material has not been contextualized for digital communication. Furthermore, it was found that the readability level of the text is still too difficult for Grade IV students, which is consistent with previous research. These findings confirm a gap between the instructional materials and student needs. It is concluded that the analyzed Grade IV Javanese Language textbook for the Kurikulum Merdeka is less relevant for use by students in the digital era.